COMPUTER CRIME AND ITS IMPACT ON WATER TRANSPORT - Bariak, Miroslav; Pogany, Maros; Zarnay, Pavel; Jurkovic, Martin (Doprava a spoje, 2011)
The aim of this contribution is to outline legal framework and important security issues related to telecommunication devices and telecommunication utilized in transportation and also to provide outputs suggesting solutions of those issues. Selected legal and information technology concerns related to the topic are being discussed as well.